The Influence of Productive Zakat Funds and Technology on the Level of Profit of Mustahik Businesses (Case Study on Baznas Makassar City) - Handayani, Lilies; Hartas Hasbi; Suriani Jihad; Aryandi (Asian Journal of Philosophy and Religion, 2023)
The purpose of this study was to (1) determine the effect of productive zakat funds on the level of profit of mustahik businesses at Baznas Makassar City. (2) To determine the effect of technology on the level of profit of mustahik businesses at Baznas Makassar City. (3) To determine the effect of productive zakat funds and technology on the level of mustahik business profits at Baznas Makassar City.This type of research is descriptive quantitative using questionnaire, interview, and documentation methods in data collection. The population in this study were all members of the productive zakat fund recipients of Baznas Makassar City as many as 30 people. This study uses saturated sampling techniques in determining the sample, where all population numbers are used as research samples. The results of the study showed that the variables of Productive Zakat Funds and Technology both partially and simultaneously had a positive and significant influence on the Mustahik Business Profit Level at Baznas Makassar City.The implication of this research is that productive zakat funds affect the level of profit of mustahik businesses, as well as technology also affects the increase in profits in businesses run by mustahik.